ANALYZING FINANCIAL PERFORMANCE OF STOCKS LISTED IN IDX (A PRE AND POST IPO OF ASTRA INTERNATIONAL, TBK.) - Rilie Tirza Liliroyor Sagai (FEB Universitas Sam Ratulangi Manado, 2023)
The aim of this research is about review whether the IPO (Initial Public Offering) influence significantly to Astra International or not by analyzing the differences of Pre and Post IPO in period 3 years ago and after. Furthermore to accomplish this research, better to describe detail about the company and analyze the financial performance by using financial performance ratio such as such as current ratio, acid-test ratio, average collection period, account receivable turnover ratio, inventory turnover, return on assets, Operating income return on investment (OIROI), operating profit margin, net profit margin, total asset turnover, fixed assets turnover, debt ratio, times interest earned, and return on common equity, current ratio, acid-test ratio, average collection period, account receivable turnover ratio, inventory turnover, return on assets, Operating income return on investment (OIROI), operating profit margin, net profit margin, total asset turnover, fixed assets turnover, debt ratio, times interest earned, and return on common equity. The sample ini this research is of this research is the years of financial consolidation data that is 3 years before and 3 years after. That means the sample size in 1987-1993. This research is using matched-pairs test for related samples requires. The results are, There is a changing in financial system of Astra International before and after going public. It drives the company to ,make a decision for go public and clears that Astra International went public in 1990. The main result is, the post IPO is better than pre IPO, it is showed by the averaging of each financial performance as independent variables. Moreover, the graph of the financial ratios showed fluctuate but tend to go uptrend. Keywords : IPO, financial performance ratios.